New information augmenting the picture of local environment at the LGM/LGT in the context of the Middle Danube region. (September 2016) - Nerudová, Zdeňka; Doláková, Nela; Novák, Jan
Records of occupation by humans in the period following shortly after the Last Glacial Maximum (LGM; 21 ± 2 kyr cal. BP) are still very rare in Central Europe, since it is inferred that the extreme climatic conditions caused the decolonisation of previously settled areas. Our study focuses on the reconstruction of environmental conditions in the surroundings of the open-air Palaeolithic site, Brno-Štýřice III, which falls within this period. The research concentrated on the study of malacological, pollen and anthracological samples to reconstruct the climate shortly after the LGM. 14 C dating places the chronostratigraphic position of the site more precisely at the end of the LGM, more specifically into Last Glacial Termination (LGT); analysis of chipped stone industry identifies the occupation with the Epigravettian settlement. The site represents a significant example of the recurrent habitation of a microclimatically favourable microregion near a watercourse in order to utilise available sources of livelihood. The results of the pollen, anthracological and malacological analyses documented a more or less treeless character of surrounding landscape. The vegetation was mostly formed by a mixture of shrub tundra and grassy loess steppe vegetation. Open woodland with birch, willow and bird cherry occurred in relatively moist river banks and the lower slopes of hills with more favourable microclimatic conditions. Malacological collection highlights the presence of cool temperate species ( Pupilla loessica, Vallonia excentrica and Helicopsis striata ). In the surroundings of the studied site, the pollen analysis provided a reconstruction of parkland forest-steppe vegetation (with lack of temperate deciduous trees) typical for a cold and dry climate. Development of both dry and moist stands near the watercourse was recorded. Anthracological analysis is in support of similar outcomes, reconstructing the presence of open woodland with dominating birch and willow in the nearby surroundings.